1877. COVID-19-Associated Hospitalizations among Long-Term Care Facility Residents Ages ≥65 Years — COVID-NET, 14 U.S. States, March 2020–January 2022. (15th December 2022) - Taylor, Christopher; Whitaker, Michael; Anglin, Onika; Pham, Huong; Patel, Kadam; Milucky, Jennifer; Reingold, Arthur; Alden, Nisha B; Meek, James; Ward, Katelyn; Teno, Kenzie; Kohrman, Alexander; et al.
Abstract: Background: Adults aged ≥65 years and those with underlying medical conditions, including residents of long-term care facilities (LTCF), are at increased risk for COVID-19-associated hospitalizations and other severe outcomes. Methods: Hospitalizations among LTCF residents aged ≥ 65 years from March 2020–January 2022 were described using data on a representative sample of hospitalizations from the CDC's COVID-19-Associated Hospitalization Surveillance Network (COVID-NET), a population-based surveillance network of > 250 acute care hospitals in 99 counties across 14 states. A Poisson regression model adjusting for age, race/ethnicity, underlying medical conditions, vaccination status, month of admission, and do-not-resuscitate/intubate-or-provide comfort-measures-only (DNR/DNI/CMO) code status examined the relationship of LTCF residency to death during COVID-19-associated hospitalization. Results: Of 11, 901 hospitalizations among adults aged ≥ 65 years reported during the study period, 2, 965 (24.9%) were LTCF residents; most resided in nursing homes (53.8%) or assisted living facilities (26.8%). LTCF residents hospitalized with COVID-19 were older and more likely to have cardiovascular disease, congestive heart failure, a neurologic condition, dementia, or ≥ 3 underlying medical conditions than non-residents (Figure). The proportion of LTCF residents vs non-residents who required intensive care unit admission or invasive mechanical ventilation were not statistically different (23.2% vs 23.5% and 10.7 vs 13.5%, respectively). The proportion of in-hospital death was higher among LTCF residents than non-residents (22.8% vs 14.4%, p < 0.01). More LTCF residents have a DNR/DNI/CMO code status (48%) compared to non-residents (19%). The fully adjusted regression model found the risk ratio for death was 1.03 (95% CI, 1.01–1.05) among LTCF residents compared to non-residents. Conclusion: Compared to non-residents, LTCF residents were older, had more underlying conditions, and had a higher risk of in-hospital death. After adjusting for multiple potential confounders, results suggest that LTCF residency is a weak but significant independent risk factor for death during COVID-19-associated hospitalization. Disclosures: All Authors : No reported disclosures.